PENGARUH PROFITABILITAS, KEPEMILIKAN MANAJERIAL, DAN ARUS KAS BEBAS TERHADAP MANAJEMEN LABA (Studi Empiris Pada Perusahaan Manufaktur Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Pada Tahun 2019-2023) - Diva Zahira, Alfina; Tarmizi, M. Irfan (Jurnal Akuntansi AKTIVA, 2025)
This study aims to examine the effect of Profitability, Managerial Ownership and Free Cash Flow on Earnings Management in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2019-2023. The design of this study is associative with a quantitative type. This study uses secondary data. The population used is the food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange. The sampling technique used purposive sampling so that 30 companies were selected as research samples. The method used is panel data regression analysis using Eviews 12 software. Determination of the model with chow data and hausman test and using regression equations, coefficients of determination and hypothesis testing. The results of this study indicate that Profitability has a positive and significant effect on Earnings Management, Free Cash Flow has a negative and significant effect on Earnings Management and Managerial Ownership has no effect on Earnings Management